Association of visceral obesity indicators with prostate cancer: a cross-sectional study from Xinjiang - Cai, Zhiruo; Guan, Xue; Xiao, Yunyun; An, Hengqing; Tao, Ning (Frontiers in Oncology, 2025)
BackgroundProstate cancer (PCa) is a common malignancy among men worldwide, and its risk is strongly associated with obesity, especially visceral obesity. Visceral obesity has been assessed by the visceral adiposity index (VAI), cardiometabolic index (CMI), and lipid accumulation product (LAP), but their associations with PCa remain underexplored. This study investigated the relationship between these visceral obesity indicators and PCa risk.MethodsData for this cross-sectional study were obtained from the First Affiliated Hospital of Xinjiang Medical University from 2022-2023, and 730 participants were screened for the study. A total of 102 PCa patients were included as the PCa group and 102 healthy individuals as the control group using propensity score matching (PSM). We collected anthropometric data (height, weight, waist circumference) and blood biochemical parameters from participants to calculate the VAI, CMI and LAP. These indicators’ association and predictive efficacy with PCa were assessed by logistic regression, restricted cubic spline (RCS), and receiver operating characteristic (ROC) curve analysis. The robustness of these results was further examined through sensitivity analyses.ResultsVAI, CMI, and LAP were higher in the PCa group than in the control group (P<0.05). Logistic regression models showed that VAI, CMI, and LAP were positively associated with PCa. This association of VAI and CMI shows robustness in sensitivity analysis. Compared with the first quartile (Q1), the fourth quartile’s (Q4) VAI, CMI and LAP were linked to an increased risk of PCa (OR: 9.07, 95% CI: 3.21-25.65; OR: 11.10, 95% CI: 3.87-31.83; OR: 3.01, 95% CI: 1.17-7.76, respectively). RCS analysis showed that VAI and CMI were nonlinearly associated with PCa risk, and LAP was linearly associated with PCa risk. The area under the ROC curve (AUC) of VAI, CMI, and LAP was 0.721 (95% CI: 0.651-0.791), 0.711 (95% CI: 0.639-0.782), and 0.593 (95% CI: 0.515-0.671), respectively.ConclusionsVisceral obesity indicators are closely associated with PCa, of which VAI and CMI show good predictive value and robustness, and can be used as potential biomarkers for assessing PCa risk.